Visual-admittance-based model predictive control for nuclear collaborative robots - Qi, Jun; Xu, Zhao; Chu, Jiru; Zhu, Minglei; Teng, Yunlong (Frontiers in Energy Research, 2023)
This paper presents a novel visual-admittance-based model predictive control scheme to cope with the problem of vision/force control and several constraints of a nuclear collaborative robotic visual servoing system. A visual admittance model considering the desired image feature and force command in image feature space is proposed. Moreover, a novel constraint scheme of the model predictive control (MPC) is proposed to cancel the overshoot in the interaction force control for most cases by taking the desired force command as the constraint of the proposed MPC. Via applying the robotic dynamic image-based visual servoing (IBVS) model, some other constraints, such as the actuator saturation, joint angle, and visual limits, can be satisfied simultaneously. The simulation results for the 2 degrees of freedom (DOF) robot manipulator with an eye-to-hand camera are present to demonstrate the effectiveness of the proposed controller.